Artists’ Pages - Ellis, Simon (The International Journal of Screendance, 2018)
No abstract available This text-based adaptation of a performance-presentation was originally published by Parallel Press, an imprint of the University of Wisconsin-Madison Libraries, as part of The International Journal of Screendance, Volume 1 (2010), Parallel Press. It is made available here with the kind permission of Parallel Press.